Secagem e armazenamento de sementes de Cordia trichotoma (Vellozo) Arrabida ex Steudel - Gusatto, Fabiane Cristina (2015)
The forest species Cordia trichotoma (Vellozo) Arrabida ex Steudel, whose seeds are classified as intolerant to desiccation, gives emphasis on the recovery of degraded areas, due to rapid growth and production of high quality wood. The sexual propagation is hindered by the loss of seed viability during the storage period. Thus, the aim of this study was to evaluate the desiccation tolerance and storage of blond-brown seeds with the use of saturated salt solutions of calcium chloride (CaCl2) and calcium nitrate (Ca(NO3)2). The blond-brown seeds were collected in the municipalities of Rondon, Guaíra and Santa Helena in 2012 and immediately transported to the Seed Technology Laboratory and seedlings, State University of West Paraná to perform the processing. Then the seeds were dried in humidity environment controlled with saline solutions, being kept in plastic boxes of higrostat type until they reach the equilibrium moisture content. Before drying, and every 90 days after drying and storage they were determined moisture content, germination percentage, germination speed index, peroxidase activity and respiratory activity. After drying, the seeds were stored in glass bottles and kept in a dry chamber with a temperature ranging from 13 to 17°C for 360 days. The seeds of the town of St. Helena had the largest diameter, germination percentage and germination speed index. Regardless of moisture content, the activities of peroxidase and respiratory enzyme did not affect the physiological potential of seeds. The enzymatic and respiratory activity can be used as indicators of the deterioration of the seeds of this species. The storage conditions of the preserved seed vigor and viability for 6 months